Juridical Analysis of Legal Protection of Personal Data in terms of Legal Certainty - Akhmad Afridho Wira P; Fitria Esfandiari; Wasis Wasis (Indonesia Law Reform Journal, 2023)
Personal data is individual data that is stored, cared for, and kept true and also protected by confidentiality. There are various kinds of rules governing personal data in Indonesia but there is no one rule that specifically regulates personal data itself. The purpose of this study is to analyze the protection of personal data in terms of legal certainty. The problem in this research is how the legal protection of personal data is viewed from the Legal Certainty Principle, as well as the ius constituendum for personal data regulation in Indonesia. This study uses normative legal research using statutory and case approaches. Collection of legal materials through the method of literature study, with primary, secondary, and tertiary legal materials. The conclusion from the results of this study shows that the current regulations still do not really provide concrete protection because personal data itself does not have laws that specifically regulate and bind it. The suggestion from this study is that there are efforts to optimize agencies or institutions that have authorization in terms of enforcing data protection laws in Indonesia. Abstrak Data pribadi adalah data perseorangan yang disimpan, dirawat, dan dijaga kebenarannya dan juga dilindungi kerahasiaanya. Terdapat berbagai macam aturan yang mengatur data pribadi tersebut di Indonesia tetapi belum ada satu aturan yang mengatur secara khusus tentang data pribadi itu sendiri. Tujuan penelitian ini adalah untuk menganalisa tentang perlindungan data pribadi ditinjau dari aspek kepastian hukum.  Permasalahan dalam penelitian ini adalah bagaimana perlindungan hukum terhadap data pribadi ditinjau dari Asas Kepastian Hukum, serta ius constituendum terhadap pengaturan data pibadi di Indonesia. Penelitian ini menggunakan penelitian hukum normatif dengan menggunakan pendekatan perundang-undangan dan pendekatan kasus. Pengumpulan bahan hukum melalui metode studi literatur, dengan bahan hukum primer, sekunder, maupun tersier. Kesimpulan dari hasil penelitian ini menunjukkan bahwa, aturan- aturan yang berlaku saat ini masih belum terlalu memberikan perlindungan yang konkrit karena data pribadi ini sendiri belum memiliki undang-undang yang khusus mengatur dan mengikat didalamnya. Saran dari penelitian ini adalah ada upaya optimalisasi terhadap instansi atau lembaga yang memiliki otorisasi dalam hal penegakan hukum perlindungan data di Indonesia.